Adsorption of 2-mercaptobenzimidazole Corrosion Inhibitor on Copper: DFT Study on Model Oxidized Interfaces. Issue 16 (7th December 2020) - Chiter, Fatah; Costa, Dominique; Maurice, Vincent; Marcus, Philippe
Abstract : High corrosion inhibition efficiency of the 2-mercaptobenzimidazole (MBI) molecule for copper in different aqueous solutions is well established. We propose a first principle DFT study of the surface chemistry of the adsorption of MBI on preoxidized Cu(111). For both thione (MBIH) and thiolate (MBI ◦ ) species, the formation of a full monolayer (ML) is favored over low coverage adsorption. At the ML coverage, the molecules adopt a perpendicular orientation with respect to the surface. MBI ◦ interaction with the surface is stronger than MBIH one. MBIH and MBI ◦ bond to the surface forming a S–Cu bond; for MBIH, the NH moiety forms a H-bond with a surface oxygen atom; for MBI ◦, a N–Cu bond is formed. For MBI ◦ at low coverage, a Cu–C bond is also formed. The charge analyses show a charge transfer between the surface and the molecule. Comparing the MBIH/MBI ◦ adsorption energies with that of water/OH, we find that MBI ◦ can replace H2 O and OH at the preoxidized Cu surface. The results are compared with those obtained with 2-mercaptobenzothiazole, a similar azole derivative with corrosion inhibition properties.